Pleomorphic adenoma of the cheek in a child: A case report - Kalenahalli Jagadishkumar; Mathod Ganeshrao Anilkumar; Halasahalli Chowdegowda Krishna Kumar; Rangaswamy Maggad (Dental Research Journal, 2014)
Salivary gland tumors are rare in children and, when they do arise, they mainly affect the major salivary glands. Minor salivary gland tumors are rare in children and are responsible for less than 10% of the cases. Pleomorphic adenoma is the most common tumor of the salivary glands. The most common sites of pleomorphic adenoma of the minor salivary glands are the palates, followed by the lips and the cheeks. Pleomorphic adenoma of the cheek is rare in children and only few cases have been reported so far.